BANKING REGULATION AND SUPERVISION IN TRADITIONAL AND ISLAMIC FINANCE: COMPARATIVE ANALYSIS AND IMPLEMENTATION FEATURES - T. Yu. Mazurina; Sh. S. Sharipov (Вестник университета, 2020)
The content of banking regulation and supervision, its structural and functional elements and features of implementation in traditional and Islamic financial systems have been revealed. Special attention to the issues of evolution of international approaches to banking regulation has been paid. The main models and tools of prudential supervision of Islamic financial institutions-Islamic audit and Sharia financial supervision authority have been characterized. The main problems of implementation of international standards in the activities of organizations providing Islamic financial services, specific features and main directions of development of the system of regulation and supervision of Islamic banks in the context of harmonization of the Supervisory process of Islamic banks and international standards of banking supervision have been analysed.